OVERVIEW OF RHEUMATOID ARTHRITIS MANAGEMENT: FROM BIOLOGICS TO NOVEL THERAPIES (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize contemporary, evidence-based strategies for rheumatoid arthritis management-from conventional synthetic DMARDs and biologics to targeted synthetic agents and emerging therapies-and translate guidance into pragmatic, patient-centered care.Methods: We reviewed the 2021 American College of Rheumatology (ACR) and 2023 European Alliance of Associations for Rheumatology (EULAR) recommendations, FDA safety communications on Janus kinase (JAK) inhibitors, pivotal head‑to‑head and long‑term trials (e.g., MTX-based treat‑to‑target, SELECT‑COMPARE, Upadacitinib vs Abatacept), and recent reports on GM‑CSF and BTK inhibition through October 17, 2025.Results: Current guidance endorses early diagnosis, shared decision‑making, and treat‑to‑target (T2T) aiming for remission/low disease activity with tight control. Methotrexate remains first‑line; short glucocorticoid courses are minimized. For inadequate response/intolerance, either a biologic DMARD (TNF, IL‑6 receptor, CTLA‑4‑Ig, anti‑CD20) or a JAK inhibitor can be added; however, JAK inhibitors carry boxed warnings for MACE, malignancy, VTE, and death, mandating risk stratification. Biosimilars broaden access without compromising outcomes. Novel strategies-GM‑CSF blockade (Otilimab) and BTK inhibitors (Fenebrutinib, BMS‑986142)-show promise in selected populations, though long‑term comparative data and positioning relative to established agents remain evolving.Conclusions: Rheumatoid arthritis care should prioritize early T2T with methotrexate anchoring therapy, prompt escalation to biologic or targeted synthetic DMARDs when not at target, vigilant safety monitoring (especially for JAK inhibitors), vaccination and infection prevention, comorbidity management, and consideration of emerging mechanisms within clinical trials.
Keywords: Rheumatoid arthritis, biologics, JAK inhibitors, treat‑to‑target, Biosimilars, emerging therapies.